Measuring the Social Responsibility and its Impact on the Financial Performance of Banks: Applied Research in the Iraqi National Bank (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The objective of the research is to measure the impact of social responsibility on the financial performance of the National Bank of Iraq for the period from 2014 to 2016 (3 years) through discussing and analyzing the level of practice of the Bank of Baghdad for social responsibility and the impact on their financial performance during the period. To measure the independent variable (CSR), the researcher used the CSR Disclosure Index and relied on the ROA as an indicator to measure the dependent variable (financial performance). The results of the research showed the main hypothesis of the research, which states that the social responsibility of the banks has no significant impact on the financial performance. In relation to the disclosure of social responsibility and ROA used. The research concluded with a number of conclusions, the study concluded a number of conclusions. The most important of these was that the adoption of social responsibility activities by the Iraqi National Bank in general was limited on the basis of the results achieved, reflecting the lack of a culture of social commitment and the consequences of its work on society and the country in which it operates. Its financial performance in general due to the results reached as it did not rise to the global benchmark associated with banking (standard ratios) according to the index used by the researcher to measure the financial performance of banks.